PEMBUATAN APLIKASI INFORMASI LAPANGAN OLAHRAGA BERBASIS ANDROID - David Setiawan Wijaya; Daniel Hary Prasetyo; Fitri Dwi Kartikasari (CALYPTRA, 2018)
Exercise is something everyone must do. Not apart from sports that can be done at home or sports that require a field. Currently there are many sports rental courts that are spread in every city. But there is no system that can connect userswith field owners. This app connects between field owners in particular basketball, badminton, soccer, volleyball and futsal with users. This app uses Phonegap that integrates with Framework7. Phonegap is a framework that allows web developers to turn it into a mobile app. Phonegap can be combined with framework7 which is an open source framework created for mobile application makers. This app also has a location feature with the help of googlemaps that serves to show the location of the sports field. With the creation of this application as well as with the results of the questionnaire can be concluded, help tenants field to find out the latest sports field information and order the field directly using thesmartphone.